2023
DOI: 10.7759/cureus.43268
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Reliability of YouTube Videos on Myocardial Infarction: A Cross-Sectional Study

Shubham Holge,
Amaresh Gogikar,
Rafiya Sultana
et al.

Abstract: Introduction: This study aims to assess the quality and reliability of the disease information available on YouTube ( www.youtube.com ) about “heart attacks” or myocardial infarctions, using a Global Quality Score (GQS) for quality, a DISCERN score for reliability, and a Video Power Index (VPI) for popularity. Methodology: In this cross-sectional observational study, the YouTube videos were analyzed in terms of the type of uploader, content, and other factors. The GQS, DISCERN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
2
6
1
Order By: Relevance
“…The analysis revealed that within the majority of the videos analyzed, 58 (82.9%) of them were uploaded more than a year ago; this suggests that perhaps the YouTube content available for gastroesophageal reflux disease is outdated. These findings are similar to the findings of a similar study conducted by Holge et al, which reported 40 videos (78.44%) [ 11 ]. Outdated information can be misleading due to advances in care and support with further research.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The analysis revealed that within the majority of the videos analyzed, 58 (82.9%) of them were uploaded more than a year ago; this suggests that perhaps the YouTube content available for gastroesophageal reflux disease is outdated. These findings are similar to the findings of a similar study conducted by Holge et al, which reported 40 videos (78.44%) [ 11 ]. Outdated information can be misleading due to advances in care and support with further research.…”
Section: Discussionsupporting
confidence: 92%
“…With adequate lifestyle changes and an understanding of how to use educational resources thoroughly, patients have the ability to combat this disease with knowledge. Various Studies have successfully proved and cited the benefits of resources such as YouTube as an asset when exploring a particular disease [ 10 , 11 ]. A patient is able to explore the possible cause and etiology, clinical presentation, symptoms, diagnosing tools and tests, prevention and vaccines, treatment options, complications, and support and management options.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, median GQS scores based on uploader type were found to be of good quality, with news channels and patients suffering from the disease having the highest median GQS scores (5, respectively). Holge et al also found that the YouTube videos they examined regarding myocardial infarction exhibited high-quality content, supported by a higher average GQS score [21]. These findings contrast those by This study also found reliability of videos was not significantly associated with uploader type, and found low median reliability scores among the various uploader types, as well.…”
Section: Discussioncontrasting
confidence: 55%
“…Our study found that 59.15% of the videos were regarding the treatment of palpitations. Similarly, Hogle et al reported that 52.94% of the videos they studied had treatment information [21]. Fewer videos we studied had content regarding support groups (4.23%).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation